Job Analysis in Employee Placement in the Organizational Bureau of the Regional Secretariat of East Java Province - Abram Cristito Purba; Oktarizka Reviandani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Human Resources (HR) play an important role in carrying out government functions, especially in terms of readiness, education level, and professionalism. Job analysis is a key element to ensure employee placement that is in accordance with the abilities, responsibilities, and needs of the organization. This study, conducted at the Organization Bureau of the Regional Secretariat of East Java Province, aims to evaluate the effectiveness of job analysis in supporting optimal employee placement. Using a qualitative descriptive method, this study found a mismatch between the needs and filling of job positions. Of the total 83 positions needed, only 35 were filled, while 48 positions were still vacant, potentially affecting organizational performance. Job analysis produces detailed information related to job descriptions and specifications, including the duties, responsibilities, and qualifications required. However, job vacancies force organizations to maximize the use of existing HR through reassignment. Some suggested solutions include increasing recruitment, developing employee competencies through training, and updating job analysis periodically. With these steps, it is hoped that the right placement of HR can improve professionalism, effectiveness, and work efficiency in the Organization Bureau. Keywords: Employee Placement, Job Analysis, Job Description,  Job Specifications